2016
DOI: 10.2147/ijn.s100625
|View full text |Cite
|
Sign up to set email alerts
|

Miconazole-loaded solid lipid nanoparticles: formulation and evaluation of a novel formula with high bioavailability and antifungal activity

Abstract: Background and objective Miconazole is a broad-spectrum antifungal drug that has poor aqueous solubility (<1 µg/mL); as a result, a reduction in its therapeutic efficacy has been reported. The aim of this study was to formulate and evaluate miconazole-loaded solid lipid nanoparticles (MN-SLNs) for oral administration to find an innovative way to alleviate the disadvantages associated with commercially available capsules. Methods MN-SLNs were prepared by hot homogenizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 25 publications
(22 reference statements)
2
45
0
Order By: Relevance
“…Conventional formulations are given in higher doses to overcome this issue and compensate for low permeability. In recent years, the use of lipid vesicles as carriers for topical drugs has attracted great attention due to their ability to overcome the barrier properties of the skin [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional formulations are given in higher doses to overcome this issue and compensate for low permeability. In recent years, the use of lipid vesicles as carriers for topical drugs has attracted great attention due to their ability to overcome the barrier properties of the skin [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported amorphization of ITCZ in various polymers, such as cellulose acetate phthalate, polyvinyl acetate phthalate, hydroxypropylmethylcellulose, hydroxypropylmethylcellulose acetate succinate and polyvinylpyrrolidone. [5][6][7] However, to our knowledge, no articles have yet been published on amorphization of ITCZ or MCZ in PLGA. Therefore, the existence of amorphized drug in ITCZ-and MCZ-PLGA MS was examined using DSC.…”
Section: Resultsmentioning
confidence: 99%
“…1,2) A number of strategies have been tried for enhancing the release rates and bioavailabilities of oral dosage forms of these antifungal drugs. [3][4][5][6][7] In injectable formulations, the use of cosolvents, such as ethanol, macrogol and propylene glycol, or surfactants, has been shown to successfully enhance the solubilization of the drugs. 8) Recently, in order to achieve sustained-release delivery, an approach using biodegradable microspheres (MS) containing antimicrobial agents or other types of drug has been tried.…”
Section: Introductionmentioning
confidence: 99%
“…The entrapment efficiency was determined by centrifugation method as reported previously . One millilitre of CD/CS‐SCU‐NPs was centrifuged at 15 000 rpm 24 400 g for 15 min (4°C), and the clear supernatant solutions were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The entrapment efficiency was determined by centrifugation method as reported previously. [23,24] One millilitre of CD/CS-SCU-NPs was centrifuged at 15 000 rpm 24 400g for 15 min (4°C), and the clear supernatant solutions were obtained. After dilution by 10-fold methanol, concentrations of SCU in the supernatant (free drug) were determined by HPLC consisting of a pump (Model LC-20A; Shimadzu, Kyoto, Japan), a reversed-phase C 18 column (150 9 4.5 mm, 3 lm) maintained at room temperature, a variable wavelength UV detector (Model SPD-20A; Shimadzu, Kyoto, Japan) at 335 nm.…”
Section: Determination Of Entrapment Efficiency Of Nanoparticlesmentioning
confidence: 99%